Practical Transfusion Medicine: Third Edition - Murphy, M; Pamphilon, D (John Wiley and Sons, 2009)
Highly Commended - 2010 BMA Medical Book Awards. An essential, practical manual for all those working in transfusion medicine. Concise and user-friendly guide to transfusion medicine. Focuses on clinical aspects but also covers background science and organizational issues. Complications encountered in transfusion are addressed throughout. Highlights controversial issues and provides advice for everyday clinical questions in transfusion medicine. This comprehensive guide to transfusion medicine takes a practical and didactic approach. The third edition of this text includes many new contributions and has expanded to seven sections. The first of these takes the reader systematically through the principles of transfusion medicine. The second deals with the complications which can arise in transfusion and is followed by a section on the practice of transfusion in blood centres and hospitals. The fourth section covers clinical transfusion practice and the fifth looks at alternatives to transfusion. Section six addresses cellular and tissue therapy and organ transplantation and the final section of the book examines the development of the evidence base for transfusion. As with previous editions; the final section includes a visionary chapter on future advances in the field. This new edition of Practical Transfusion Medicine benefits from even more international authorship than the previous two editions and is an invaluable resource for trainee doctors, scientists, technicians and other staff in haematology and transfusion and as a reference book for clinical staff in haematology and other disciplines faced with specific problems. © 2009 Blackwell Publishing Ltd.